Youth athletes` perception of autonomy support from the coach, peer motivational climate and intrinsic motivation in sport setting: One-year effects - Joesaar, H.; Hein, V.; Hagger, M. S. (Psychology of Sport and Exercise, 2012)
Objectives: Grounded in self-determination theory (SDT; Deci & Ryan, 1985) and achievement goal theory (AGT; Nicholls, 1989), the present study examined the temporal stability and reciprocal relationships among three key variables related to motivation: perceived autonomy support from the coach, task-involving peer motivational climates, and athletes` intrinsic motivation. Design: A prospective longitudinal design with data collected on two occasions one year apart over the course of a youth training season. Method: Young athletes (N = 362, age range 11-16 years) completed measures of the Sport Climate Questionnaire and the Peer Motivational Climate in Youth Sport Questionnaire. One-year later participants completed these questionnaires again along with the Sport Motivation Scale. Results: Structural equation modeling indicated that perceived autonomy support from the coach and task-involving peer motivational climates exhibited comparatively high stability over a one-year period. In cross-lagged analyses, perceived autonomy support from the coach positively predicted task-involving peer climate one-year later but not vice versa. In addition, both social factors demonstrated a significant direct effect on athletes intrinsic motivation measured concurrently in sport contexts. Further, an alternative structural model supported a longitudinal direct effect of autonomy support from the coach and task-involving peer climate measured on the first occasion on subsequent intrinsic motivation. Conclusion: Results demonstrated the value of perceived autonomy support from the coach and task-involving peer motivational climate in predicting athletes` intrinsic motivation over a training year. Findings also suggest that perceived autonomy support from the coach can facilitate later task-involving peer motivational climate.